Smart food grain storage system using Internet of Things (IoT): A Review - Priyadarsani, Supriya; Pradhan, Asit Kumar; Jena, Prakash Chandra (ORYZA-An International Journal of Rice, 2023)
India is one of the largest producers of food grains in the world. The country has a diverse agricultural sector that produces a wide range of crops, including rice, wheat, maize, pulses (such as lentils and chickpeas), and oilseeds. Rice and wheat are considered essential for ensuring food security in India. India has an extensive network of food grain storage infrastructure to cater to its significant agricultural production. The storage infrastructure in India is primarily managed by the Food Corporation of India (FCI), state government agencies, and private sector entities. Some of food grain storage infrastructure in India are warehouses, covered storage structures (silos), mandi storage facilities (temporarily store grains) and strategic reserve (buffer stock for food security). Private sector entities are increasingly investing in the modern storage facilities including temperature-controlled warehouses and automated storage systems, to improve storage capacity and reduce post-harvest losses. India faces challenges in effectively managing and maintaining the quality of stored food grains. Issues such as inadequate storage capacity, insufficient maintenance, lack of proper pest control measures, and logistical constraints contribute to post-harvest losses. The government and other stakeholders are continuously working on improving storage infrastructure and implementing technological solutions to address these challenges that tiggers for spoilage, mold growth, insect infestation and excessive drying. The real time monitoring and controlling of these factor during the storage period is a cumbersome task and needs advanced techniques. In this aspect Internet of Things (IoT) offers numerous benefits to food grain storage systems including real-time monitoring, early warning systems, optimal environmental conditioning, energy efficiency, inventory management, traceability and predictive analytics. By leveraging IoT technology, the industry can improve storage practices, reduce losses, ensure food safety, and enhance the overall efficiency of grain storage operations.